Strategi Pembelajaran Inovatif: Modul IPA berorientasi PBL untuk meningkatkan prestasi siswa di SD Muhammadiyah Inovatif Mertoyudan - Pramudianti, Rizki; Supriyoko, Supriyoko; Hasan, Moch Zainal Arifin (Bulletin of Educational Management and Innovation, 2024)
Background: Schools currently need more interactive and effective learning methods to improve student learning outcomes. Problem Based Learning (PBL) was chosen as an approach because this method encourages students to think critically and solve problems, which is expected to improve their understanding and learning outcomes. Purpose: The aim of this research is to improve student learning outcomes through module development and to determine the feasibility and effectiveness of using the module. Method: This study uses the R & D (Research & Development) approach. The development includes an initial trial of 3 validators, that are field trials are limited to 15 students and 2 teachers and the operational field trialas many as 23 students. The nstruments that used are questionnaire, observation, interview, and test. The operational field trial uses the design of one group pre-test and post-test. The learning outcomes data with a paired t-test sample are used to determine the differences in learning outcomes while the increase in learning outcomes is calculated through normalized n-gain. Findings: Based on the results of the study, it can be concluded as follows: 1) the science module oriented Problem Based Learning (PBL) on the material nature of objects to improve student learning outcomes refers to Borg & Gall which is modified into nine stages namely research and information collection, planning, initial product design, initial trials, initial product revisions, limited field trials, second product revisions, operational field trials, third product revisions. 2) The feasibility modules oriented on PBL is based on the assessment of material experts, learning experts, media experts, practitioners of education in general obtain very good classification. 3) Development science modules oriented on PBL in material properties of objects can improve student learning outcomes indicated by an average increase of 0.54 calculated through n-gain.